A Case Report Describing a Rare Presentation of Simultaneous Occurrence of MPO-ANCA-Associated Vasculitis and Rheumatoid Arthritis - Nathalie Foray; Tamer Hudali; Muralidhar Papireddy; John Gao (Case Reports in Nephrology)
Background. Renal-limited myeloperoxidase vasculitis with simultaneous rheumatoid arthritis is reported as a rare occurrence. Review of literature suggests that most patients had a diagnosis of rheumatoid arthritis for several years prior to presenting with renal failure from myeloperoxidase vasculitis. Case Presentation. A 58-year-old Caucasian male presented to the hospital experiencing malaise, fevers, decreased oral intake, nausea, and vomiting for one week duration. His past medical history consisted of newly diagnosed but untreated rheumatoid arthritis, hypertension, and non-insulin-dependent diabetes mellitus. He was found to have acute renal failure, proteinuria, and hypoglycemia. Standard therapy, including intravenous fluids, did not improve his acute renal failure. A vasculitis workup resulted in a positive myeloperoxidase anti-neutrophil cytoplasmic antibody (MPO-ANCA). Renal biopsy revealed crescentic glomerulonephritis (GN) pauci-immune type, suggestive of MPO-ANCA-associated vasculitis (MPO-AAV). Treatment consisted of prednisone, cyclophosphamide, and seven cycles of plasmapheresis, in addition to hemodialysis for uremia. Upon discharge, he received hemodialysis for another week and continued treatment with cyclophosphamide and prednisone. Conclusion. Patients with longstanding rheumatoid arthritis may develop renal failure due to nonsteroidal anti-inflammatory medication use and AA type amyloidosis; however, necrotizing glomerulonephritis with crescent formation has been rarely reported. This stresses the importance of early recognition and swift initiation of treatment.